Evaluating the Effect of 18O Incorporation on the Vibrational Spectra of Vaterite and Calcite - Helen E. King; Aleksandar Živković; Nora H. de Leeuw (Crystals, 2022)
Calcium carbonates are critical in biomineralization processes and as functional materials. For many applications, isotope enrichment in these materials allows researchers to monitor reaction pathways and retrace environmental signatures. When using vibrational spectroscopy, isotopic composition is currently derived by summing the concentration of each isotopologue, assumed to be directly obtainable from the band intensity, divided by the content of the isotope within the different isotopologues (e.g., C16O3, C16O218O, C16O18O2 and C18O3). However, this approach relies on the assumption that each isotopologue band has an equivalent intensity when present at the same concentration within the crystal structure. Here, using a joint experimental and theoretical approach we test the spectral behavior of the O-isotopologues by examining the effect of a key isotopic tracer, 18O, on the vibrational spectra of the calcium carbonate phases calcite and vaterite. We demonstrate that isotopic substitution changes both band positions and band intensities to different extents, depending on the vibrational spectroscopy method used and the bands examined. For calcite, the υ1 symmetrical stretching Raman-active bands related to individual isotopologues are found to have very similar intensities and are not affected by changes in isotopologue distribution within the material. Fitting these bands resulted in a consistent underestimation of the isotopic enrichment of only 1%, thus they are expected to be useful for estimating 18O-enrichment extent in future experimental work. In contrast, vaterite vibrational bands change more extensively and thus cannot be used directly to determine the 18O concentration within the material. These results are expected to contribute to a deeper und less ambiguous understanding of evaluating isotopic enrichment effects in the vibrational spectra of calcium carbonates.